The Effectiveness of Using LKPD on Circle Material to Improve Students' Numeracy Skills - Siti Magfiroh; Nafida Hetty Marhaeni (EDUTREND: Journal of Emerging Issues and Trends in Education, 2024)
Numeracy is the ability to apply number concepts, calculation operation skills, and the ability to explain information or problems using Mathematics. The purpose of this research is to determine the effectiveness of using Reciprocal Teaching-based Worksheets (LKPD) to enhance students' numeracy in circle material. This type of research is an experiment with a pretest and posttest design. The sample in this study consisted of students from class XI F2 at SMA N 4 Yogyakarta. Data collection techniques included interviews, observations, and numeracy skills test questions for students. The results of this research indicate that the use of Reciprocal Teaching-based LKPD is effective in improving students' numeracy skills. Therefore, this research concludes that the use of Reciprocal Teaching-based LKPD is effective in improving students' numeracy skills in circle material.